Phonology of Anuek Jamee as Spoken at Labuhanhaji - Muchsin Muchsin (Serambi Tarbawi, 2013)
This research oriented the phonology of Anuek Jamee as spoken at Labuhanhaji. This research is focused for phonology and intends to see the process of phonology Anuek Jamee by using especially Anuek Jamee at Labuhanhaji. From the research analysis the writer found that the result was different from the Anuek Jamee at Labuhanhaji with the other places by using the Anuek Jamee language. In addition, the writer meant to add collection about the linguist of Anuek Jamee.